2015
DOI: 10.1155/2015/945901
|View full text |Cite
|
Sign up to set email alerts
|

Yang/Qi Invigoration: An Herbal Therapy for Chronic Fatigue Syndrome with Yang Deficiency?

Abstract: According to traditional Chinese medicine (TCM) theory, Yang and Qi are driving forces of biological activities in the human body. Based on the crucial role of the mitochondrion in energy metabolism, we propose an extended view of Yang and Qi in the context of mitochondrion-driven cellular and body function. It is of interest that the clinical manifestations of Yang/Qi deficiencies in TCM resemble those of chronic fatigue syndrome in Western medicine, which is pathologically associated with mitochondrial dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…The mechanism of yang-xu constitution is pathologically associated with mitochondrial dysfunction [24], impaired thermogenesis [25], or loss of the effectiveness of the pituitary-adrenal axis [26]. Clinical study suggests that T2DM patients with Yang deficiency BC were less likely to present with diabetic retinopathy [5].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of yang-xu constitution is pathologically associated with mitochondrial dysfunction [24], impaired thermogenesis [25], or loss of the effectiveness of the pituitary-adrenal axis [26]. Clinical study suggests that T2DM patients with Yang deficiency BC were less likely to present with diabetic retinopathy [5].…”
Section: Discussionmentioning
confidence: 99%
“…In general, symptom differentiation is a key component of KM-based diagnosis and treatment. One group proposed the usefulness of symptom differentiation strategy to treat this illness using herbal drugs, such as Cistanches Herba and Schisandrae Fructus for CFS patients with Yang deficiency 37) . A systematic review also reported the possibility of acupuncture or moxibustion as a potential treatment for CFS 38) .…”
Section: New Naming and Perspectives For Cfsmentioning
confidence: 99%
“…Studies have shown that chronic fatigue was most common among women and caucasians and signi cantly related to depression, mixed anxiety and depressive disorder, and generalized anxiety disorder [9] .The etiology and pathogenesis of fatigue are largely unknown. In recent years, researchers have been exploring various therapeutic measures such as acupuncture and moxibustion [10],spa therapy [11] and chinese herbal medicine [12] .There is still a lacking of objective and effective comprehensive evaluation methods for the diagnosis of fatigue, which leads to the inability to carry out targeted interventions when fatigue occurs in the early stage of disease. Hence it is imperative to establish a comprehensive objective evaluation method for fatigue.…”
Section: Introductionmentioning
confidence: 99%